2004
DOI: 10.1017/s0952523804041045
|View full text |Cite
|
Sign up to set email alerts
|

Visual experience promotes the isotropic representation of orientation preference

Abstract: Within the visual cortex of several mammalian species, more circuitry is devoted to the representation of vertical and horizontal orientations than oblique orientations. The sensitivity of this representation of orientation preference to visual experience during cortical maturation and the overabundance of cardinal contours in the environment suggest that vision promotes the development of this cortical anisotropy. We tested this idea by measuring the distribution of cortical orientation preference and the deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 78 publications
(238 reference statements)
1
38
0
Order By: Relevance
“…He might not be surprised to find out that the role sensory activity plays in the development and maintenance of the nervous system turns out to be an incredibly intractable problem. For example, some complex computed sensory modules, like orientation maps in visual cortex, develop normally without the benefit of sensory input, while other modules that coexist in the same cortical volume, such as visual direction domains, have an absolute requirement for visual experience [104, 116, 117]. …”
Section: Discussionmentioning
confidence: 99%
“…He might not be surprised to find out that the role sensory activity plays in the development and maintenance of the nervous system turns out to be an incredibly intractable problem. For example, some complex computed sensory modules, like orientation maps in visual cortex, develop normally without the benefit of sensory input, while other modules that coexist in the same cortical volume, such as visual direction domains, have an absolute requirement for visual experience [104, 116, 117]. …”
Section: Discussionmentioning
confidence: 99%
“…In the primary visual cortices of several species including cats (Pettigrew et al, 1968;Kennedy and Orban, 1979;Orban and Kennedy, 1981;Payne and Berman, 1983;Li et al, 2003;Wang et al, 2003aWang et al, , 2003b, ferrets (Chapman et al, 1996;Coppola et al, 1998b;Chapman and Bonhoeffer, 1998;Coppola and White, 2004;Grabska-Barwińska et al, 2009), and non-human primates (Mansfield, 1974;Poggio and Fischer, 1977;De Valois et al, 1982;Kennedy et al, 1985), there is generally (though not always: see Xu et al, 2006;Shen et al, 2014) a greater proportion of cells tuned to the cardinal orientations than to the oblique ones; something also observed in the purportedly homologous area of some avian species (Liu and Pettigrew, 2003;Ng et al, 2010). In addition to this numerical advantage, tuning functions are also sharper for those neurons showing a cardinal orientation preference (Rose and Blakemore, 1974;Nelson et al, 1977;Orban and Kennedy, 1981;Li et al, 2003), while recordings of mass electrical activity at the scalp in humans and monkeys show greater mean evoked potentials for cardinal compared to oblique orientations (Maffei and Campbell, 1970;Freeman and Thibos, 1975;Mansfield and Ronner, 1978;Zemon et al, 1983;Moskowitz and Sokol, 1985).…”
mentioning
confidence: 87%
“…One of the most conspicuous functional properties of neurons in the visual cortex is orientation selectivity, as more cortical circuitry represents cardinal orientations rather than oblique orientations. The development of this feature is primarily under endogenous control (e.g., Chapman, Stryker, & Bonhoeffer, 1996; Coppola & White, 2004; Wiesel & Hubel, 1974), but can also be altered by visual experience, sometimes with dramatic effects (e.g., Blakemore & Van Sluyters, 1975; Crair, Gillespie, & Stryker, 1998; Sengpiel, Stawinski, & Bonhoeffer, 1999). Specifically, an early electrophysiological study of monkeys (Wiesel & Hubel, 1974) and a recent optical imaging study of ferrets (Coppola & White, 2004) have demonstrated that overrepresentation of cardinal orientations in the visual cortex does not require experience of an anisotropic visual environment.…”
Section: Visual Experience: the Critical Why Of Perceptual Asymmetriesmentioning
confidence: 99%
“…This is consistent with prior electrophysiological (Blakemore & Van Sluyters, 1975) and later optical imaging results (Sengpiel et al, 1999). The development of orientation selectivity does not require visual experience, but is critically dependent on spontaneous neuronal activity (Chapman, Gödecke, & Bonhoeffer, 1999; Coppola & White, 2004). Absence of normal visual experience can block spontaneous neural activity and hence orientation selectivity.…”
Section: Visual Experience: the Critical Why Of Perceptual Asymmetriesmentioning
confidence: 99%